THE ROLE AND POSSIBILITIES OF DIGITAL TECHNOLOGIES IN VOCATIONAL EDUCATION - Mirzaeva Nigora Muydinovna; Olimova Munisa Erkinjon kizi; Umarova Faridakhon Nabijon kizi; Abdusalomova Gulnozakhon Dilshodovna (Web of Journals Publishing, 2025)
This article examines the role and opportunities of digital technologies in vocational education within the context of Uzbekistan’s ongoing digital transformation. Employing a mixed-methods research approach, the study analyzes quantitative and qualitative data from vocational institutions to evaluate the impact of digital tools such as e-learning platforms, virtual reality, and interactive simulations on student engagement and skill acquisition. The findings reveal significant improvements in learning outcomes and highlight the challenges related to infrastructure, educator readiness, and policy implementation. Grounded in both international and local perspectives, the research offers scientific insights and practical recommendations to optimize digital integration in vocational training. The study underscores the importance of strategic investments in infrastructure, teacher training, and public-private partnerships to ensure inclusive and sustainable digital education that aligns workforce competencies with the demands of the digital economy.
Keywords: Digital technologies, vocational education, skill development, e-learning, virtual reality, teacher training